Early dengue diagnosis by nonstructural protein 1 antigen detection: Rapid immunochromotography versus two the enzyme-linked immunosorbent assay kits - Selvaraj Stephen; Marie Victor P Charles; Velmurugan Anitharaj; Civamany Deepa; Sivaraman Umadevi (Wolters Kluwer Medknow Publications, 2014)
Dengue is known for its serious life-threatening complications. New rapid kits available recently in India target circulating non-structural protein (NS1) antigen from day one onwards. The sensitivity and specificity of a newly introduced rapid combo kit against two conventional ELISA kits is assessed. The performance of this kit is quite satisfactory since excellent agreement of 94.26% was observed with particular reference to NS1 antigen detection among all three kits namely Rapid SD Bioline dengue Duo (SD Korea), InBios DENV Detect NS1 ELISA, USA and dengue Early ELISA, Panbio, Australia. The false positivity of the rapid kit is very low since its specificity as for as NS1 antigen detection is concerned is 98.33%. The use of combination kit helps to detect additional cases of dengue, which are negative for NS1 antigen but positive for IgM and/or IgG antibodies, thus facilitating early diagnosis in remote areas and small laboratorie